Intolerance for approach of ambiguity in social anxiety disorder. Issue 4 (19th May 2017) - Kuckertz, Jennie M.; Strege, Marlene V.; Amir, Nader
ABSTRACT: Previous research has utilised the approach–avoidance task (AAT) to measure approach and avoidance action tendencies in socially anxious individuals. "Neutral" social stimuli may be perceived as ambiguous and hence threatening to socially anxious individuals, however it is unclear whether this results in difficulty approaching ambiguous ("neutral") versus unambiguous threat (e.g. disgust) faces (i.e. intolerance of ambiguity) . Thirty participants with social anxiety disorder (SADs) and 29 non-anxious controls completed an implicit AAT in which they were instructed to approach or avoid neutral and disgust faces (i.e. pull or push a joystick) based on colour of the picture border. Results indicated that SADs demonstrated greater difficulty approaching neutral relative to disgust faces. Moreover, intolerance for approach of ambiguity predicted social anxiety severity while controlling for the effects of trait anxiety and depression. Our results provide further support for the role of intolerance of ambiguity in SAD.